Lower Cardiovascular Reactivity Is Associated With More Childhood Adversity and Poorer Midlife Health: Replicated Findings From the Dunedin and MIDUS Cohorts. (September 2021) - Bourassa, Kyle J.; Moffitt, Terrie E.; Harrington, HonaLee; Houts, Renate; Poulton, Richie; Ramrakha, Sandhya; Caspi, Avshalom
Cardiovascular reactivity has been proposed as a biomarker linking childhood adversity and poorer health. In the current study, we examined the association of childhood adversity, cardiovascular reactivity, and health in the Dunedin Multidisciplinary Health and Development Study ( n = 922) and Midlife in the United States (MIDUS) studies ( n = 1, 015). In both studies, participants who experienced more childhood adversity had lower cardiovascular reactivity. In addition, people with lower cardiovascular reactivity had poorer self-reported health and greater inflammation. Dunedin participants with lower cardiovascular reactivity were aging biologically faster, and MIDUS participants with lower heart rate reactivity had increased risk of early mortality. Cardiovascular reactivity was not associated with hypertension in either study. Results were partially accounted for by greater reactivity among more conscientious, less depressed, and higher functioning participants. These results suggest that people who experienced childhood adversity have a blunted physiological response, which is associated with poorer health. The findings highlight the importance of accounting for individual differences when assessing cardiovascular reactivity using cognitive stressor tasks.